2003
DOI: 10.1536/jhj.44.963
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Carvedilol on Calcium Channels in Vascular Smooth Muscle Cells.

Abstract: SUMMARYCarvedilol has hypotensive effects and inhibits agonist-induced cell proliferation of vascular smooth muscle and then prevents vascular remodeling. However, the basic mechanisms have not been clarified. release from store sites induced by thapsigargin, but significantly inhibited the sustained rise due to capacitative Ca 2+ entry unrelated to I Ca.L . In contrast, metoprolol did not mimic these effects of carvedilol. These results provide evidence that carvedilol inhibits I Ca.L and may also inhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…19) In our study, we observed a reduction in blood pressure in both patient groups with carvedilol 6.25 mg and 25 mg, but not in the 12.5 mg group. This may be due to different etiologies and left ventricular reserves.…”
Section: Discussionsupporting
confidence: 43%
“…19) In our study, we observed a reduction in blood pressure in both patient groups with carvedilol 6.25 mg and 25 mg, but not in the 12.5 mg group. This may be due to different etiologies and left ventricular reserves.…”
Section: Discussionsupporting
confidence: 43%
“…In the same way, a reduction of Ca 2+ -ATP pump activity affects electrolyte removal from cytosol, reducing parietal elasticity. 27,28 Carvedilol seems to restore Ca 2+ homeostasis and remove actomyosin complex, improving active relaxation. These ancillary actions could explain the observed diastolic restoration and changes in LV filling pattern.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased of intracellular Ca 2+ concentration will elicit relaxation. The previous study has suggested that Carvedilol exhibited the inhibitory effects on Ca 2+ mobilization and this unique action may contribute to its antihypertensive effect [3]. Using KEGG database and literature mining, we have linked the intracellular metabolic variations to the vascular smooth muscle relaxation pathway (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Carvedilol, a nonselective β -antagonist ( β 1 , β 2 ), has proven potent antihypertensive activity and also effective in the treatment of coronary artery disease and congestive heart failure [2]. It also possesses calcium channel blocking effect by inhibiting voltage-dependent L-type Ca 2+ in vascular smooth muscle cells [3]. Carvedilol has an asymmetric carbon atom, which gives rise to S - and R -enantiomers.…”
Section: Introductionmentioning
confidence: 99%